Literature From The Margins: a study on the relevance of zines - de Carvalho, Nathalia Rodrigues; Tarran, Fernanda Martinez (Revista PHILIA | Filosofia, Literatura & Arte, 2019)
The scope of this research is to study the zine, which is a handmade booklet. The purpose is to reflect on what the zine is, discussing its format, reflecting on where it is inserted in the publishing market and what its cultural relevance is. This study is a theoretical and bibliographic research with a qualitative approach. We analyze three zines – Geração Beat, by Renato Alessandro dos Santos, O Ceifador de Privilégios, by Arthus Mehanna, and Libertemo-nos, by Melina Bassoli – in order to understand their format, the ways of production, where they are inserted, and their themes. Afterwards, we notice characteristics that contribute to the dissemination of culture and democratic values, thus becoming an object of great cultural relevance. Keywords: Zine. Marginal Literature. Publishing market.